PERAN KEPUASAN DALAM MEMEDIASI DETERMINAN LOYALITAS NASABAH DALAM MENGGUNAKAN E-BANKING PADA BANK SUMSEL BABEL SYARIAH - Dwiyanti, Julita; Umari, Zuul Fitriani; Aryanti, Aryanti (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2023)
The research entitled The Influence of Security, Knowledge, and Convenience on Customer Loyalty in Using E-banking Products at Bank Sumsel Babel Syariah KC Palembang Through Satisfaction as an Intervening Variable. The purpose of this study was to analyze the effect of security, knowledge, and convenience on customer loyalty in using M-banking at the Sumsel Babel Syariah KC Palembang bank with satisfaction as the intervening variable. In this study the population used was all customers at Bank Sumsel Babel Syariah KC Palembang who were registered as BSB Mobile users. The research sample was taken as many as 100 people with the Random Sampling technique using the Hair et al formula. In this study a quantitative approach was used using data collection techniques by distributing questionnaire data. Data analysis techniques using SPSS 26.0 software tools. The results of this research variable Security has no effect on Customer Loyalty, Knowledge has no effect on Customer Loyalty, Convenience has an effect on Customer Loyalty, Satisfaction has an effect on Customer Loyalty, Security has no effect on Satisfaction, Knowledge has no effect on Satisfaction, Convenience has no effect on Satisfaction, Security has an effect on Customer Loyalty with Satisfaction as a mediating variable, Knowledge has an effect on Customer Loyalty with Satisfaction as a mediating variable, Convenience has an effect on Customer Loyalty with Satisfaction as a mediating variable.